Strategies for reward-based crowdfunding campaigns - Sascha Kraus; Chris Richter; Alexander Brem; Cheng-Feng Cheng; Man-Ling Chang (Journal of Innovation & Knowledge (JIK), 2016)
Crowdfunding represents an alternative way of funding entrepreneurial ventures - and is attracting a high amount of interest in research as well as practice. Against this background, this paper analyzes reward-based crowdfunding campaign strategies and their communication tools. To do this, 446 crowdfunding projects were gathered and empirically analyzed. Three different paths of successful crowdfunding projects could be identified and are described in detail. Practical implications of crowdfunding strategies are derived, and are dependent on the required sales effort and the project added value. The terms communicator, networker and self-runner are created for this crowdfunding strategy and filled with practical examples. This paper contributes to the literature in different ways: first, it sheds more light on the developing concept of crowdfunding, with an overview of current academic discussions on crowdfunding. Furthermore, the analysis of success factors for crowdfunding initiatives adds to an emerging area of research and allows entrepreneurs to extract best practice examples for increasing the probability of successful crowdfunding projects under consideration of the key influencing factors of communication.
Keywords: M13; O03; O31; O32; 650; Crowdfunding; Reward-based; Success factors; Germany; fsQCA; Communication